First Results From a Propensity Matching Trial of Mycophenolate Mofetil vs. Azathioprine in Treatment-Naive AIH Patients - Dalekos, George N.; Arvaniti, Pinelopi; Gatselis, Nikolaos K.; Samakidou, Anna; Gabeta, Stella; Rigopoulou, Eirini; Koukoulis, George K.; Zachou, Kalliopi (Frontiers in Immunology, 2022)
Background/Aims As previous real-world studies and meta-analyses have shown that mycophenolate mofetil (MMF) might have better efficacy than azathioprine (AZA) in autoimmune hepatitis (AIH), we conducted a propensity matching study to assess the efficacy and safety of MMF vs. AZA. Methods All 126 consecutive treatment-naive adult AIH patients, diagnosed and followed in our department since 2016, were included. Patients received prednisolone 0.5–1 mg/kg/day plus either AZA 1–2 mg/kg/day or 1.5–2 g/day MMF. The tapering of prednisolone was identical between groups. Results After propensity matching score and adjustment for known factors affecting response to treatment and outcome, 64 patients were included in the study (MMF = 32 and AZA = 32). Rates of non-response, complete biochemical response (CBR) at 6 and 12 months, and prednisolone withdrawal (6 months, 12 months, and end of follow-up) were identical between groups. However, MMF treatment was significantly associated with CBR at the end of follow-up [odds ratio (OR) 11.259; 95% CI: 1.3–97.4, p = 0.028]. AZA patients were more prone to stop treatment due to AZA intolerance/insufficient response (p = 0.0001). At the end of follow-up, the overall efficacy of each schedule was also significantly higher in the MMF group compared to the AZA group (p = 0.0001). Conclusion We showed for the first time in a propensity matching study that MMF can be used as first-line therapy in AIH as attested by the significantly higher CBR at end of follow-up compared to AZA. Whether this better efficacy is also associated with higher histological remission rates and sustained CBR off immunosuppression needs further evaluation.